Continuous Flow Injection Analysis Method for the Determination of a Drug Diphenhydramine Hydrochloride by Using Phosphomolybdic Acid - Muntadhar M. Jabbar; Elham N. Mezaal (مجلة بغداد للعلوم)
The study presented a new method for determining diphenhydramine hydrochloride (DPH) in its pure form and some pharmaceutical preparations, within CFIA technique. The method is simple, fast, sensitive, easy to operate, and of a low cost. It is based on the reaction of DPH with phosphomolybdic acid (PMA), in aqueous media, forming a white, slightly yellowish precipitate. The precipitate formed was studied using an Ayah 6S×1-ST-2D solar cell CFI analyzer, by the reflection of incident light off the surfaces of the deposited particles at (0–180°), expressed as the response measured in (mV) . Some chemical and physical variables were studied to provide optimal conditions for the study. The linear range was 0.07-9  mmol/L and it had a correlation coefficient (r) with a value of (0.9998). The limit of detection (L.O.D.) of the new method was 729.55 ng/sample, calculated by gradually diluting the lower limit of the concentration in the linear range (0.07 mmol/L). The % RSD was less than 0.2% for a concentration of 0.1, 4.0 and 10.0 mmol/L of DPH for n = 8. The method was successfully applied in the determination of DPH in three samples from three different pharmaceutical production companies. Using the standard addition method, the new method was compared with the UV-Vis spectrophotometry method at λmax = 258 nm. Both T-test and F-test. The results of the two tests showed no significant difference at a confidence level (95%).